2021
DOI: 10.1016/j.ejca.2021.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Regional lymphadenopathy following COVID-19 vaccination: Literature review and considerations for patient management in breast cancer care

Abstract: Purpose Over 1 billion doses of COVID-19 vaccines have been already administered across the US, the UK and the EU at the time of writing. Furthermore, 1.82 million of booster doses have been administered in the US since 13 th August, and similar booster programmes are currently planned or under consideration in the UK and the EU beginning in the autumn of 2021. Early reports showed an association between vaccine administration and the development of ipsilateral axillary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
52
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 39 publications
(45 reference statements)
1
52
0
Order By: Relevance
“…A literature review of data from 15 studies involving >2,000 patients with breast cancer showed that the incidence of vaccine-induced lymphadenopathy ranges from 14.5% to 53%. This lymphadenopathy persisted for >6 weeks in 29% of patients 153 . Radiation recall phenomena, such as pneumonitis or dermatitis, have been described following COVID-19 vaccination [157][158][159] .…”
Section: Toxicitiesmentioning
confidence: 96%
See 1 more Smart Citation
“…A literature review of data from 15 studies involving >2,000 patients with breast cancer showed that the incidence of vaccine-induced lymphadenopathy ranges from 14.5% to 53%. This lymphadenopathy persisted for >6 weeks in 29% of patients 153 . Radiation recall phenomena, such as pneumonitis or dermatitis, have been described following COVID-19 vaccination [157][158][159] .…”
Section: Toxicitiesmentioning
confidence: 96%
“…Local lymphadenopathy commonly occurs after COVID-19 vaccination. Vaccine-induced lymphadenopathy found on CT or PET could be mistaken for lymph node metastases in certain patients, such as those with breast cancer or melanoma [153][154][155][156] , although unlike cancer, the lymph node enlargement usually completely resolves spontaneously 139 . A literature review of data from 15 studies involving >2,000 patients with breast cancer showed that the incidence of vaccine-induced lymphadenopathy ranges from 14.5% to 53%.…”
Section: Toxicitiesmentioning
confidence: 99%
“…Additionally, as the COVID-19 vaccines gradually released to the public in the first year of the pandemic, the vaccination coverage (at least one shot) had been administered to approximately 60% of the eligible population worldwide. [5] Cases of lymph nodes enlargement after vaccination for weeks to months, especially axillary and supraclavicular lymphadenopathy had been noticed [6,7]. Most of the cases of lymphadenopathy were discovered by regular follow-up imaging studies [8].…”
mentioning
confidence: 99%
“…Findings from mammography, sonography over neck or breast, computed tomography, or magnetic resonance imaging were all possible. There was a broad consensus that the COVID-19 vaccination should not be postponed even considering the worry of cancer survivor follow-up imaging [6]. However, recommendations varied by countries.…”
mentioning
confidence: 99%
See 1 more Smart Citation